The role of universities in efforts to increase the added value of recycled bucket tooth products through product design methods - Widiyawan Kristiyanto; Sajidan Sajidan; Suranto Suranto; Saputro Herman (Open Engineering)
The role of universities in managing the potential recycling of low-carbon steel waste into renewable bucket tooth products represents an innovative effort to conserve natural resources, with positive social and environmental impacts. This research, conducted in Solo, Indonesia, involves collaboration among universities, metal foundry small and medium-sized enterprises (SMEs), and the mining industry as product users. A mixed-method approach, combining grounded theory and quantitative analysis, was used to assess the role of universities in this partnership. The university’s role is focused on product design, adopting the reduce–reuse–recycle–redesign (R4) approach. This role has contributed to reducing metal scrap generation from local mining companies, an average of 1,620.5 tons annually. This added economic value reflects the integration of supply positively impacted the growth of local metal foundry SMEs by 5.73% in 2019.